Quizizz dalam Pembelajaran PAI: Pengaruh Game-Based Learning terhadap Motivasi Belajar Peserta Didik - Alif Dhio Putra; Wan Jamaluddin; Uswatun Hasanah (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
Student learning motivation in Islamic Religious Education remains a significant challenge, particularly when instructional activities are conducted conventionally and provide limited opportunities for active participation. Such learning conditions may reduce students’ enthusiasm, engagement, and willingness to understand the learning materials. This study aimed to examine the effect of the Quizizz-based Game-Based Learning model on students’ learning motivation in Islamic Religious Education at SMK Negeri 7 Bandar Lampung. A quantitative approach was employed using a quasi-experimental method with a posttest-only control group design. The research sample consisted of two Grade X classes. The experimental class received instruction using the Quizizz-based Game-Based Learning model, whereas the control class was taught using conventional instructional methods. Data were collected after the intervention through a learning motivation questionnaire developed using a Likert scale. The data were analyzed using normality, homogeneity, and independent-samples t-tests with SPSS. The results indicated that the data were normally distributed and homogeneous. The t-test produced a significance value of 0.001, which was lower than 0.05, demonstrating a statistically significant difference in learning motivation between the experimental and control classes. Therefore, the Quizizz-based Game-Based Learning model significantly influenced students’ learning motivation in Islamic Religious Education. These findings suggest that integrating gamification through Quizizz can provide a more engaging, interactive, and relevant learning experience for students in the digital era.